The Effect of Work Environment, Work Ability, and Work Discipline on Work Performance in Companies of BPJS Kesehatan - Rosida, Elvina; Wajdi, M. Farid (SAFE-Network, 2023)
The aim of this research is to investigate the effect of the work environment, employee ability, and work discipline on Work Performance. This study employed a quantitative approach using non-probability sampling and a method of purposive sampling. This study's samples consisted of one hundred respondents who were disseminated by Google from the BPJS offices in Surakarta and Sukoharjo. Using the smartPLS application, outer model and inner model analysis are used to handle these study data. The results of this research show that the work environment, work ability, and work discipline have a positive and statistically significant effect on Work Performance.